(untitled) (American Journal of Technology and Applied Sciences, 2024)
The article deals with the practical issue of managing the educational process on the example of the hydropower industry. A mathematical model of the problem was created using the principle of systematic approach of management theory and the elements of set theory. A calculation algorithm for solving the problem is created, the results of the calculation experiment are presented, and practical recommendations are given.